2004
DOI: 10.1300/j073v15n04_03
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand Travel Agent Practice in the Provision of Advice for Travel to Risky Destinations

Abstract: Travel agents are one of the most important influencing factors in the travel decision-making process. In terms of safety, there is a growing expectation that travel agents should, as do tour operators, assess destination safety even more critically than a member of the general travelling public. However, the provision of safety advice by travel agents is challenged by the increasingly complex and competitive environment in which they work. Travel safety, while looming large in the thoughts of the general trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
(23 reference statements)
2
27
0
1
Order By: Relevance
“…The fi ndings from Lovelock's (2003) study on agents' travel safety advice mirror that of previous research into health advice (Lawton & Page, 1997) where generally poor (or lack of) advice is given by travel agents. A common theme across research into travel health advice is the argument used by travel agents that they are not doctors and it is not their business to provide detailed health information (Dawood, 1989;Lawton & Page, 1997).…”
Section: Role Of Travel Agents In Ethical Travelsupporting
confidence: 63%
See 3 more Smart Citations
“…The fi ndings from Lovelock's (2003) study on agents' travel safety advice mirror that of previous research into health advice (Lawton & Page, 1997) where generally poor (or lack of) advice is given by travel agents. A common theme across research into travel health advice is the argument used by travel agents that they are not doctors and it is not their business to provide detailed health information (Dawood, 1989;Lawton & Page, 1997).…”
Section: Role Of Travel Agents In Ethical Travelsupporting
confidence: 63%
“…This research was built upon previous work undertaken within New Zealand and abroad focusing upon health advice or safety advice provided by travel agents (Lawton & Page, 1997;Lovelock, 2003). While there has been an emphasis on health and safety, to date there has been little empirical research (especially in New Zealand, but abroad too) that has examined the political aspects of travel advice.…”
Section: Aims Of the Articlementioning
confidence: 99%
See 2 more Smart Citations
“…The outcome from their research revealed that travel risks were being dismissed by travel agents with no detailed health information being given. In a survey of New Zealand travel agents, Lovelock (2004) found that perceptions of destination safety were not reflected in the travel agent's behaviour with respect to selling travel packages. This was put down to a number of possible reasons: that the travel agent would probably not be travelling there so feel less personal risk, the relationship between the travel agent and client and client profile, and the influence of external information sources.…”
Section: Promotion and Awareness Of Riskmentioning
confidence: 99%